Variability of the helical axis during active cervical movements in people with chronic neck pain. (February 2019) - Alsultan, Feras; Cescon, Corrado; De Nunzio, Alessandro Marco; Barbero, Marco; Heneghan, Nicola R.; Rushton, Alison; Falla, Deborah
Abstract: Background: Recent work described parameters of the helical axis in asymptomatic people with potential for investigating kinematic changes in the cervical region. This approach could provide novel information on movement variability in people with neck pain, however this has never been investigated. This study aimed to investigate movement variability during active neck movements performed at different speeds in people with and without chronic neck pain. Methods: This observational case-control study examined 18 participants with chronic neck pain of either idiopathic or traumatic origin and 18 gender-matched asymptomatic participants. Cervical kinematics were captured with 3D motion capture as people with and without chronic neck pain performed flexion-extension, bilateral lateral flexion and bilateral rotation at different speeds (natural, slow, and fast). The mean distance and mean angle parameters of the helical axis were extracted to describe 3D motion and quantify movement variability. Findings: A smaller mean distance was observed in those with neck pain compared to the asymptomatic participants during flexion-extension ( P  = 0.019) and rotation movements ( P  = 0.007). The neck pain group displayed smaller values for the mean angle during rotation movements with different speeds ( P  = 0.01). These findings indicate less variable movement for those with neck pain relative to the asymptomatic participants. No difference in the mean angle was observed between groups for flexion-extension and lateral flexion. Interpretation: The findings reiterate the importance of data derived from kinematic measures, and its potential for providing clinicians with further insight into the quality of active neck movements in people with chronic neck pain. Highlights: Examines movement variability in people with neck pain via parameters of the helical axis Decreased movement variability was observed in people with chronic neck pain. Movement variability decreased with higher levels of fear of movement.